Isolasi dan identifikasi metabolit sekunder dari ekstrak butanol pegagan [Centella asiatica (L) urban] - Dian Herlinda Octorina Howan (Jurnal Kimia Fullerene, 2017)
A triterpenoid tetrahydroxy of 3.1 mg has been isolated from the butanol extract of Centella asiatica. Separation and purification were performed using several stages of column chromatography, and identification was performed by taking the proton nuclear magnetic resonance spectrum (NMR-1H). The spectral data of NMR-1H isolate F6.1 indicates the presence of signals at a chemical shift (δ in ppm) 0.89 (d, J = 6.35 Hz), 0.94 (d, J = 6.35 Hz), 1.05 (s), 1.06 (s), 2 CH3, 1.12 (s), 2 hydroxy methylene protons at δ 3.78 (t; J = 4.88 Hz), and 3.99 (t J = 4.88 Hz), 3 methyl protons attached to the hydroxylated carbon each at δ 4.24 (m), 4.22 (m), and 3.72 (d; J = 10.7 Hz) Based on RMI-1H spectrum data it can be proposed that isolate F6.1 is brahmic acid, 2α, 3β, 6β, 23-tetrahydroxy-28-oat-12en.